2020
DOI: 10.3390/nu12010164
|View full text |Cite
|
Sign up to set email alerts
|

Herba houttuyniae Extract Benefits Hyperlipidemic Mice via Activation of the AMPK/PGC-1α/Nrf2 Cascade

Abstract: Hyperlipidemia is associated with metabolic disorders, but the detailed mechanisms and related interventions remain largely unclear. As a functional food in Asian diets, Herba houttuyniae has been reported to have beneficial effects on health. The present research was to investigate the protective effects of Herba houttuyniae aqueous extract (HAE) on hyperlipidemia-induced liver and heart impairments and its potential mechanisms. Male C57BL/6J mice were administered with 200 or 400 mg/kg/day HAE for 9 days, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Huang et al [ 51 ] showed that promoting AMPK phosphorylation and upregulation of PGC1α expression had a neuroprotective role by attenuating oxidative stress and neuronal apoptosis in a hypoxic–ischemic encephalopathy rat model. As a master antioxidant regulator, Nrf2 was regulated by the AMPK/PGC1α-signaling pathway [ 52 , 53 ]. Recent studies have reported that activation of AMPK exerted a protective effect in ferroptosis-associated renal ischemia/reperfusion injury [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al [ 51 ] showed that promoting AMPK phosphorylation and upregulation of PGC1α expression had a neuroprotective role by attenuating oxidative stress and neuronal apoptosis in a hypoxic–ischemic encephalopathy rat model. As a master antioxidant regulator, Nrf2 was regulated by the AMPK/PGC1α-signaling pathway [ 52 , 53 ]. Recent studies have reported that activation of AMPK exerted a protective effect in ferroptosis-associated renal ischemia/reperfusion injury [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the extracts have been found to significantly reduce NO, PGE-2, TNF-α, and IL-6 levels [ 20 ]. In addition, H. cordata extract inhibited the generation of ROS in TNF-α stimulated human keratinocyte cells and activated Nrf2, along with the subsequent induction of antioxidative enzymes [ 21 , 22 ]. H. cordata contains a wide range of polyphenols, such as rutin, quercetin, hyperoside, quercitrin, and chlorogenic acid, which are known to be responsible for its pharmacological activity, including its anti-inflammatory and antioxidative properties [ 17 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, NRF2 and PPARG were downregulated in hyperlipidemic mouse livers and hearts, which may be attributable to the loss of PRKAA2 activity. All of these changes were reversed by Herba houttuyniae supplementation [ 90 ]. Curcumin increases HO-1 via activation of NRF2, inducing to attenuation of HFD-induced elevations of malonedialdeyde (MDA) and ROS in skeletal muscle but not in adipose tissue or liver [ 91 , 92 ].…”
Section: Nrf2 and Cardiovascular Risk Factorsmentioning
confidence: 99%
“…Several pieces of evidence showed that the main source of ROS is vascular wall, mainly through mitochondrial electron transport chain activity, NOX1, xanthine oxidase, and uncoupled nitric oxide synthase (NOS) (reviewed in [ 17 ]). Vascular cells produce ROS when stimulated by cytokines, ANG II, EDN1, aldosterone, and PDGF, favoring oxidative modifications of redox-sensitive proteins, such as calcium-calmodulin kinase, ryanodine receptor, and sarcoplasmic reticulum ATPase, thus altering their conformation, stability, activity, and ability to react with other proteins and modulate vascular function (reviewed in [ 90 ]). ROS generation is important to preserve endothelial and vascular smooth muscle cells function, vascular tone, responses related to inflammation process, cell growth, proliferation, apoptosis, and angiogenesis (reviewed in [ 112 ]).…”
Section: Role Of Oxidative Stress and Inflammatory Response In Cvdmentioning
confidence: 99%